Harnessing the value of near-term actions for achieving climate-ready fishery management - Drexler, Michael; Cerny-Chipman, Elizabeth B.; Peterson Williams, Megan J.; Moore, Meredith; Ridings, Corey (Frontiers in Marine Science, 2025)
Climate change requires managers to bolster long-term resilience of fisheries and concurrently improve short-term responsiveness of management systems to prevailing ecological conditions, all while avoiding unintended harm to stocks in a highly uncertain context. There has been substantial effort dedicated to developing the scientific information and tools needed to inform climate-ready fisheries, yet implementation of these approaches has been limited in the United States management system. Meanwhile, climate impacts on fisheries are already occurring, making fish and fishing communities highly vulnerable to sudden, and often detrimental, changes. There is a need to accelerate adaptation efforts, and near-term action is critical even without the full complement of information and tools in hand. Here, existing climate-ready approaches were compiled and synthesized to offer a comprehensive and structured perspective on priority actions that can be taken in the next 1-2 years to increase the resilience and adaptability of fish stocks and communities that rely on them. From the review there are three main findings: 1) 45% of the management actions can be implemented in this short timeframe, 2) Nearly all actions identified can be implemented in the current fishery and regulatory framework, and 3) While new approaches are needed, managers should proceed with caution to avoid maladaptation and choose a no- or low- maladaptation risk approach wherever possible.